Harga dan Lokasi terhadap Keputusan Pembelian di Perumahan Griya Alam Nusantara Tipe 36/72 - Moh. Heriski Ramadan; Erni Yuningsih; Endang Silaningsih (IPM2KPE, 2024)
This research aims to identify the impact of marketing variables (price and location) on consumer purchasing decisions. The research method used was non-probability sampling using a questionnaire as an instrument to collect data from 163 respondents. The research results show that simultaneously, price and location have a positive and significant effect on purchasing decisions, with an R Square value of 59.8%. The remaining 40.2% was influenced by other factors not examined in this study. Partially, price and location also have a significant influence on purchasing decisions. The research results show that the location variable has a greater influence than the price variable on purchasing decisions in Griya Alam Nusantara Type 36/72 housing. The conclusion is that in the context of Griya Alam Nusantara Type 36/72 housing, both price and location are crucial factors that need to be considered in determining consumer purchasing decisions. Keywords: Price, Purchase Decision, Location